New Therapeutic Approaches for the Treatment of Migraine - Rattanamanee, Kwanchai (Journal of Basic and Applied Pharmacology, 2015)
MigraiMigraine is a common and highly disabling neurological disorder, associated with a significant reduction of quality of life and also impact on social functioning. The management of migraine patients is often unsatisfactory because the acute treatment of attacks has been limited to NSAIDs and combination of ergotamine-caffeine. The development of the triptans dramatically improved the acute treatment of migraine attacks. However, some patients do not respond desirably to the medicines and cardiovascular comorbidities limit their usage. Patients with migraine highly need a new therapeutic approach which should have rapid onset, longer duration of action, be better tolerated and lack of vasoconstriction activity. This review focuses on future pharmacological target and compounds which have been developed for the acute attacks of migraine including: serotonin 5-HT1F receptor agonists, nitric oxide synthase inhibitors, calcitonin gene-related peptide (CGRP) receptor antagonists, cation channel subfamily vanilloid member 1 (TRPV1) receptor modulators, glutamate receptors antagonists and PAC1 receptor antagonists. These compounds may be potentially viable anti-migraine drugs in the future.